Persuasion tactics used in corporate and activists’ communication - Arti, Alina (2023)
Persuasion or persuasive attempts are inevitable part of human communication. The process of convincing someone to change their attitude, belief, or behavior is vital for corporate communication. Scholars have been researching persuasion as a phenomenon to understand triggers that alter human’s behavior, attitudes, and beliefs. Many persuasion theories are widely applied in marketing and corporate communication. The role of persuasion in communication can be positive or negative. When used for unethical purposes, persuasion can lead to manipulation and exploitation. In recent years, the phenomenon of misinformation has risen big concern in the society. Misinformation appears and is spread by various sources: news media, companies, offline and online gossip, etc. (Swire-Thompson & Lazer, 2019). In many cases, misinformation is so powerful due to its high persuasiveness that triggers audiences to alter their behaviors, thoughts, and beliefs. This study aims to understand the usage of persuasion tactics by different actors when talking about the same case accused of misinformation. To approach this phenomenon, a theoretical framework of persuasive tactics in misinforming messages was created. Later the framework is used to evaluate the selected case: KLM and Fossielvrij NL communication about Fly Responsibly campaign that was accused of misinformation. The objective of the research is to understand which persuasion tactics are utilized by the company and activists to communicate about the case accused of misinformation and compare persuasion tactics used to see the approaches chosen to persuade the audience. The nature of this study is a qualitative study with an abductive approach. The empirical data was collected through netnography of two webpages created by the company and activists that specifically addressed the Fly Responsibly campaign. Data was analyzed through content analysis applying the developed framework. Based on the results, it based visible that company and activists used different persuasion tactics in their communication. The company was creating a vision of KLM being a partner helping customers, appear likable and acting in a socially encouraged manner. Whilst activists through their communication portray KLM as an authority that can be seen as an expert by others, and consequently, mislead them by “overusing” their trust.